Hukm Naql A'da'i Mahdur al-Dam min Manzur Islami - Ahmad Al-Suwaehi Syulaibek (Universitas Darussalam Gontor, 2012)
This research deals with an important issue, namely: (provisions of transferring organs of executed), it has been divided to: introduction, preface, and three section: The Researcher discuss in the preface: the concept of transfer of human organs, showed the meaning of transportation, the organ, and the meaning of organ transplants. The concept of the executed, its types, showed the meaning of shed, and the executed, and its types. And search in second section: transfer organs of a living person to another, showed the rule of transferring individual organ, and organs of non-individual. An discussed in the third section: Transfer of organs of the executed to another human being, showed the rule of eating the executed when necessary, and the rule of transferring of organs of the executed, and the rule of reconciliation of the executed on the transfer of its organs in exchange for not killing him, starting the opinions of jurists and their evidence, and discuss the evidence and weighting between opinions. The Researcher concluded that it is permissible to transfer organs of the executed and put it in an human body protected blood near death, under certain conditions to be met, and it is permissible to reconcile the infidel military and spy to waive for not killing him.